Continuous management of rice residue for reducing fertilizer use in rice-wheat system - Kang, J. S.; Kaur, Jagroop; Manhas, S. S. (Indian Farming, 2025)
Sustainability of rice-wheat system is crucial for the future of agriculture in Indo-Gangetic plains (IGP) as it feeds about 1/5th of world population. A major concern in the state of Punjab is management of rice residue as crop is mechanically harvested with combine harvesters leaving behind sizeable amount of residues in the field. Burning of crop residues causes several ill effects on human, livestock, soil health and environment. Crop residue management plays an important role in determining distribution and availability of nutrients in cropped soils. Under long-term residue treated soils, equivalent crop yield can be realized by using less quantity of chemical fertilizers. Slow decomposition of paddy straw containing 5-8 kg nitrogen (N), 0.7-1.2 kg phosphorus (P), 12-17 kg potassium (K), 0.5-1.0 kg S, 40-70 kg Si alongwith 400 kg of organic carbon per tonne of straw helps in enhancing the soil fertility through nutrient recycling. So, in-situ crop residue management is an alternative to improve the physical, chemical and biological properties of soil for sustainable rice-wheat production along with environment conservation.